Influence of state participation on business conditions and entrepreneurship in the EU countries of the former eastern bloc - Ada Domańska; Robert Zajkowski (e-Finanse: Financial Internet Quarterly, 2018)
The purpose of this paper is to show the extent to which state interference in the economy affects the conditions of functioning for small and medium-sized enterprises in economies of the former eastern bloc which have already gone through the EU accession process. The data on SMEs' situation were taken from the Fact Sheets of the EU program Small Business Act. Due to the fact that the variables proposed to describe the business environment differ significantly it was necessary to standardize them. The zero unitarization method was applied to rank countries properly. Special attention in this paper is devoted to Poland and the situation of businesses operating in this country. The research has identified some areas requiring urgent changes. It is crucial to improve the situation so that companies can play a proper role in the economy. A country which could be an example of good solutions that support business development is also described.
Keywords: L26; O57; P20; 330; SMEs; Small Business Act; former Eastern Bloc